Rascally signs in sacred places : the politics of culture in Nicaragua - Whisnant, David E., 1938- (H. Eugene and Lillian Youngs Lehman series., 1995)
"Anthropology meets cultural studies (popular and otherwise) and historiography with a remarkable theoretical and investigative depth. A wide range of topics includes the title essay on 19th-century culture; culture under Somoza (the elder) and resistance to that culture; Sandinista culture and resistance thereto; 19th-century looting of antiquities; gender; the political cultures surrounding Rubén Dario and Augusto Sandino; and effective introductory and concluding remarks"--Handbook of Latin American Studies, v. 57.